Zinc oxide nanoparticles alleviate chromium-induced oxidative stress by modulating physio-biochemical aspects and organic acids in chickpea (Cicer arietinum L.) - Deepti Singh; Sharma, Nathi Lal; Singh, Dharmendra; Siddiqui, Manzer H.; Sarkar, Susheel Kumar; Rathore, Abhishek; Prasad, Saroj Kumar; Gaafar, Abdel-Rhman Z.; Hussain, Sadam (Elsevier, 2024)
Extensive chromium (Cr) release into water and soil severely impairs crop productivity worldwide. Nanoparticle (NP) technology has shown potential for reducing heavy metal toxicity and improving plant physicochemical profiles. Herein, we investigated the effects of exogenous zinc oxide NPs (ZnO-NPs) on alleviating Cr stress in Cr-sensitive and tolerant chickpea genotypes. Hydroponically grown chickpea plants were exposed to Cr stress (0 and 120 μM) and ZnO-NPs (25 μM, 20 nm size) twice at a 7-day interval. Cr exposure reduced physiochemical profiles, ion content, cell viability, and gas exchange parameters, and it increased organic acid exudate accumulation in roots and the Cr content in the roots and leaves of the plants. However, ZnO-NP application significantly increased plant growth, enzymatic activities, proline, total soluble sugar, and protein and gas exchange parameters and reduced malondialdehyde and hydrogen peroxide levels, Cr content in roots, and organic acid presence to improve root cell viability. This study provides new insights into the role of ZnO-NPs in reducing oxidative stress along with Cr accumulation and mobility due to low levels of organic acids in chickpea roots. Notably, the Cr-tolerant genotype exhibited more pronounced alleviation of Cr stress by ZnO-NPs. These findings highlight the potential of ZnO-NP in regulating plant growth, reducing Cr accumulation, and promoting sustainable agricultural development.